The English language abilities of Grade R learners in an English-medium South African classroom : is there a correlation between objective measurements and teacher and parent perceptions? - Grove, Agneta Alison (Stellenbosch : Stellenbosch University, 2019)
Thesis (MA)--Stellenbosch University, 2019.